ABOUT THE IDENTIFICATION OF SOME Trichoderma ISOLATES REPORTED IN REVISTA DE PROTECCIÓN VEGETAL - Martínez, B.; Infante, Danay; Reyes, Yusimy (Revista de Protección Vegetal, 2010)
Dear Sr. Some papers concerning isolates of the antagonistic fungus Trichoderma from the Mycological Collection of the Centro Nacional de Sanidad Agropecuaria (CENSA) have been published in Revista de Protección Vegetal (from Vol. 5, No 1-3, 1990, to Vol. 24, No. 1, 2009) and other journals such as Fitopatología, Phytopathology, Cultivos Tropicales or presented in congresses, seminaries and conferences . In these papers, these isolates have been referred with numbers since their classification into species by morphology has been very difficult. Recently, the isolates referred with the numbers 1, 3, 12, 13, 17, 25, 28, 56, 75, 78, 79, 85 y 90 were taxonomically placed in the species Trichoderma asperellum Samuels using molecular methods. From now on, these isolates will be referred with the species and the corresponding number.